THE CHARACTERIZATION OF THE MAIN CHARACTER IN GONE GIRL FILM - Cindy Putri (State University of Medan, 2018)
This article deals with the characterization of the main character in Gone Girl film. The study was aimed to find outthe characterizations and the most dominant characteristic of Amy Elliot Dunne in thefilm. The study was conducted by applying descriptive qualitative method. The data of the study were taken from all utterances of Amy’s dialogues and monologues which were transcribed into 39 selected sentences. The findings of the study were: (1) the kinds of Amy characterizations: intelligent(17.94%), perfectionist (12.82%), insecure(28.20%), liar (33.33%)and vengeful(7.69%);(2) the most dominant characteristic of Amy was liar(33.33%).Keywords: characterization, characteristic, main character, film.